Condiciones que presenta el caserío de cuyuchugo, distrito de usquil, provincia de otuzco, región la libertad para la práctica del turismo vivencial - Gómez Rodriguez, Diana Carolina (2015)
This Tourism Research Project called conditions presented by the village of Cuyuchugo, Usquil District, Province of Otuzco, La Libertad; to practice experiential tourism. "In this perspective, the traditional craft practices, the provision of the Receiving Community and accessibility were studied. Which after being evaluated, the results showed that the hamlet of Cuyuchugo presents conditions for the practice of experiential tourism, because the traditional craft is one of the revenue generating activities of this community, and artisans and community were willing to participate in this type of tourism also were affordable to receive tourists in their homes and teach them all about the craft, on the other hand the state of roads are in good condition, as well as units of the four companies Of transport. Synthetic, genetically, inductive , For this research, ethnographic analytical deductive method is used, in terms of the techniques used were direct observation, registration, surveys, interviews, each with its instrument and field notebook, camera, survey questionnaire, interview guide and textual records.